Pengaruh Online Promotion dan Online Customer Review Terhadap Keputusan Pembelian Kamar di UNP Hotel dan Convention Center Padang - Taufit Hidayad; Feriantano Sundang Pranata (Varied Knowledge Journal, 2026)
In order to influence consumer purchasing decisions, hotels are being forced by the increasingly competitive nature of the hospitality business to enhance their digital marketing strategies, especially through online promotions and user review management. The purpose of this study is to examine how hotel reservations at the UNP Hotel & Convention Center in Padang are affected by online advertising and customer evaluations, both independently and in combination. This study employed a quantitative method with a causal-associative design. 98 individuals were chosen for the sample using purposive sampling; information was gathered through a questionnaire and multiple linear regression was used for analysis. The findings demonstrate that room purchasing decisions are positively and significantly impacted by internet advertisements and customer reviews. Online advertising and customer reviews account for 85.9% of the variance in purchase decisions, whereas factors beyond the purview of this study account for 14.1%. Additionally, online promos had less of an impact than customer ratings, suggesting that these reviews are the main factor that customers take into account when choosing a hotel. Both factors have a substantial impact on purchasing decisions at the same time. The relative contributions of online promotions and customer reviews to decision-making are empirically supported by this study.